[Kościół Mariacki w Gdańsku] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia kościół Najświętszej Marii Panny w Gdańsku, widok od płn.-wsch., ok. 1910 r.